2020
DOI: 10.1186/s12967-020-02531-5
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic profiling of pre-gestational and gestational diabetes mellitus identifies novel predictors of pre-term delivery

Abstract: Background Pregnant women with gestational diabetes mellitus (GDM) or type 2 diabetes mellitus (T2DM) are at increased risks of pre-term labor, hypertension and preeclampsia. In this study, metabolic profiling of blood samples collected from GDM, T2DM and control pregnant women was undertaken to identify potential diagnostic biomarkers in GDM/T2DM and compared to pregnancy outcome. Methods Sixty-seven pregnant women (21 controls, 32 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 50 publications
(45 reference statements)
0
15
0
Order By: Relevance
“…Insulin resistance, low‐grade inflammation, and endothelial cell dysfunction are considered its characteristic features. Increasing studies highlight the importance of metabolite alterations in GDM, and most efforts are focused on investigating biomarkers that could facilitate prediction and diagnosis 17–19 . These studies suggested that changes in maternal metabolic status tend to affect the levels of various metabolites and metabolic homeostasis in the fetus and subsequently lead to an increased complication of pregnancy, such as macrosomia.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Insulin resistance, low‐grade inflammation, and endothelial cell dysfunction are considered its characteristic features. Increasing studies highlight the importance of metabolite alterations in GDM, and most efforts are focused on investigating biomarkers that could facilitate prediction and diagnosis 17–19 . These studies suggested that changes in maternal metabolic status tend to affect the levels of various metabolites and metabolic homeostasis in the fetus and subsequently lead to an increased complication of pregnancy, such as macrosomia.…”
Section: Discussionmentioning
confidence: 99%
“…Increasing studies highlight the importance of metabolite alterations in GDM, and most efforts are focused on investigating biomarkers that could facilitate prediction and diagnosis. 17 , 18 , 19 These studies suggested that changes in maternal metabolic status tend to affect the levels of various metabolites and metabolic homeostasis in the fetus and subsequently lead to an increased complication of pregnancy, such as macrosomia. However, the characteristics and molecular mechanism of metabolites in the maternal‐fetal microenvironment of GDM are still unclear.…”
Section: Discussionmentioning
confidence: 99%
“…5 ). Higher levels of branched-chain amino acids (BCAA) valine, leucine and isoleucine have been detected in blood from women with GDM and are linked to an increased risk of glucose intolerance, early pathogenesis of type 2 diabetes and a high relative abundance of intestinal pro-inflammatory species of Prevotella 67 70 . The role of Prevotella spp.…”
Section: Discussionmentioning
confidence: 99%
“…Metabonomic is a powerful tool for elucidating the mechanism of metabolic abnormalities in susceptible individuals by systematically studying low molecular weight compounds in biological tissues and body fluids (Ceja-Gálvez et al, 2020;Perng et al, 2017). Metabonomic has been used to find biomarkers to predict, diagnose and monitor a variety of metabolic diseases, such as GDM (Diboun et al, 2020;Fanos et al, 2013).…”
Section: Introductionmentioning
confidence: 99%